Effect of slaughter age and post-mortem days on meat quality of longissimus and semimembranosus muscles of Boer goats. (May 2021) - Abhijith, Archana; Warner, Robyn D.; Ha, Minh; Dunshea, Frank R.; Leury, Brian J.; Zhang, Minghao; Joy, Aleena; Osei-Amponsah, Richard; Chauhan, Surinder S.
Abstract: This study investigated the effects of age of animal and days post-mortem (PM) on meat quality of Boer goats. Twenty-four (24) wether Boer goats of two age groups (2YO group: 2 years old and 9MO: 6–9 months, with 12 animals/group) were slaughtered in a commercial processing plant. The pH@Temp18 was estimated to be above 6 in both age groups with higher ( P  < 0.01) values in 2YO goats. The PM storage for 14 days reduced the shear force in both age groups ( P  < 0.01). 2YO goat muscles ( longissimus and semimembranosus ) exhibited higher ( P  < 0.01) Thiobarbituric acid reactive substance values (TBARS), indicating increased lipid oxidation. Glycogen (P < 0.01) and lactate content (20 min post-slaughter) in longissimus of 9MO were lower compared to 2YO, and total muscle glycogen concentration was lower ( P  < 0.01) in both age groups below the threshold levels. Hence, as hypothesized, age and days PM proved to play crucial roles on Boer meat quality.